A sore throat after endotracheal intubation in Sanglah General Hospital 2017 - Sobhana Shanmuganathan; Kadek Agus Heryana Putra; I Made Agus Kresna Sucandra; Putu Kurniyanta (Intisari Sains Medis, 2020)
Background: Cuff volume additionally impacts a postoperative sore throat and dysphagia. The rate of a sore throat has likewise been discovered to be higher in the event of Laryngeal Mask Airway (LMA) than that of endotracheal intubation (ETT).Aim: To know the duration of a sore throat and level of severity of a sore throat after endotracheal intubation among patients of Sanglah General Hospital.Method: This cross sectional study was conducted on patients of Sanglah General Hospital. There were 100 students were participated in this study. They were asked to fill up a self-administered questionnaire. The variables assessed were their duration towards patients who have used anesthetic during surgery.Result: About 54% of 100 patient of Sanglah General Hospital, respectively had a sore throat for 4 to 6 days after endotracheal intubation. However, 28% of patients had a sore throat from day one to day three after the endotracheal intubation method. For the severity of a sore throat over 50% of the patients have experienced pain in eating, drinking, talking and for some people it has given them an enormous side effect towards their daily activity. Though the overall duration and severity of a sore throat among the patient, lasted less than a week and for the severity patient have voted respectively high. Patients with good diet control after the surgery tend to heal faster.